Development of cognitive diagnostic assessment instruments and a cognitive differentiation student worksheet to measure and improve scientific literacy capability - Joko Supriono; Pramudiyanti; Fatkhur Rohman; ⁠Undang Rosidin (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
This research develops cognitive diagnostic assessment instruments and cognitively differentiated worksheets designed to enhance students' scientific literacy in science learning. Using a Research and Development (R&D) approach based on the Plomp model, the study involved 28 students, each from Class IV A and IV B at MIN 1 North Lampung. Data was collected through documentation, questionnaires, interviews, and observation, and analyzed using t-tests, practicality tests, and product validation. Expert validation showed the instruments and worksheets were highly valid, with average scores of 92% for cognitive diagnostic assessment questions, 94% for post-test questions, and 94% for material, linguistic, and media validation. The practicality test showed educators' responses at 84% and students' at 87%, both rated as very practical. A t-test revealed a significant difference (p = 0.001, p < 0.05) between the experimental and control classes in post-test scores. The results indicate that the developed cognitive diagnostic assessment instruments and differentiated worksheets are valid, practical, and effective in enhancing students' scientific literacy.